Surgical management of ciliary body melanoma - Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The aim was to report my own experiences of the surgical treatment of ciliary body melanoma. 42 patients were treated by trasnscleral resection of melanoma between January 1995 and June 2001. Additional rutenium brachytherapy was performed in 29 cases. Intraoperative complications included bleeding (3 cases), vitreous loss (4) and retinal detachment (2). Residual tumor in one case was the reason of enucleation. Cataract surgery and intraocular lens implantation was necessary in 7 cases. Postoperative filtration bleb appeared in 6 eyes. The evaluation of functional results has shown no impairment of visual acuity in 56% of cases and did not change during follow up. These observations show that transscleral resection with additional brachytherapy is a method of choice in the management of ciliary body melanoma.